2008
DOI: 10.1152/ajprenal.00126.2008
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 mediates the uterine capsaicin-induced NMDA NR2B-dependent cross-organ reflex sensitization in anesthetized rats

Abstract: Spinal cord-mediated cross-organ sensitization between the uterus and the lower urinary tract may underlie the high concurrence of obstetrical/gynecological inflammation and chronic pelvic pain syndrome characterized by urogenital pain. However, the neural pathway and the neurotransmitters involved are still unknown. We tested the hypothesis that the excitation of capsaicin-sensitive primary afferent fibers arising from the uterus through the stimulation of transient receptor potential vanilloid 1 (TRPV1) indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 91 publications
(104 reference statements)
1
26
0
Order By: Relevance
“…In the last decade, studies have demonstrated that the interactions between EphBRs and their ephrinB ligands modulate neural plasticity induction in the mammalian central nervous system, mainly, but not exclusively, via exhibiting effects on NMDAR (8,12). A recent study also demonstrated that, in association with thermal hyperalgesia, EphBR activation caused by immunoglobulin fusion protein of ephrinB2 (ephrinB2-Fc)-induced, Src kinase-dependent NR2B phosphorylation in the spinal cord (2), suggesting that ephrinB2-EphBR tyrosine kinase interactions could probably modulate pain signaling via spinal Src-dependent NMDAR phosphorylation (2).Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, studies have demonstrated that the interactions between EphBRs and their ephrinB ligands modulate neural plasticity induction in the mammalian central nervous system, mainly, but not exclusively, via exhibiting effects on NMDAR (8,12). A recent study also demonstrated that, in association with thermal hyperalgesia, EphBR activation caused by immunoglobulin fusion protein of ephrinB2 (ephrinB2-Fc)-induced, Src kinase-dependent NR2B phosphorylation in the spinal cord (2), suggesting that ephrinB2-EphBR tyrosine kinase interactions could probably modulate pain signaling via spinal Src-dependent NMDAR phosphorylation (2).Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
“…Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on pelvic-urethra reflex, using intact spinal cord preparations, have demonstrated a glutamatergic N-methyl-D-aspartate (NMDA)-dependent spinal reflex potentiation in which the activity of this reflex was dynamically potentiated by repetitive (29) and tetanic (30) afferent inputs. Because pathological potentiation in this reflex activity was suggested to underlie the hyperactive urethra (10, 11, 26 -28), the activity-dependent spinal reflex potentiation seems to be a novel animal model for studying urethra continent function (12,13,28,39,(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…Cross-sensitization between the bladder and other pelvic viscera is a clinical concern that makes diagnosing and treating the etiology difficult (Berkley, 2005, Baranowski et al, 2008, Theoharides et al, 2008, van de Merwe et al, 2008. In humans and in animals, the organs that seem to be most often involved in pelvic cross-sensitization besides bladder and colon, with respect to spinal afferents, appear to be the pelvic urethra and the uterus (Dmitrieva et al, 2001, Giamberardino et al, 2001, Dmitrieva and Berkley, 2002, Morrison et al, 2006, Peng et al, 2008a, Peng et al, 2008b, Peng et al, 2009). …”
Section: Electrophysiological Properties Of Ng Neuronsmentioning
confidence: 99%